2018
DOI: 10.1111/vsu.13110
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methohexital and propofol as induction agents for evaluation of laryngeal function in healthy dogs

Abstract: Objective To determine the influence of propofol or methohexital, with and without doxapram, on the examination of laryngeal function in dogs. Study design Experimental study. Animals Forty healthy dogs randomly assigned to 4 groups: propofol with saline (n = 10), propofol with doxapram (n = 10), methohexital with saline (n = 10), or methohexital with doxapram (n = 10). Methods Propofol and methohexital were administered to effect. Investigators examined laryngeal function (initial) simultaneously with video l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Only one of the studies included dogs with suspected laryngeal paralysis, in a non-blinded, non-randomised design [17]. Most studies (83%) provided a direct comparison between anaesthetic drugs, with two studies including a control group [10,13]. A total of 58% of studies evaluated laryngeal function objectively by measurement of the normalised glottal gap area (NGAA) or normalised rima glottides surface area (RGSA) via video laryngoscopy.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Only one of the studies included dogs with suspected laryngeal paralysis, in a non-blinded, non-randomised design [17]. Most studies (83%) provided a direct comparison between anaesthetic drugs, with two studies including a control group [10,13]. A total of 58% of studies evaluated laryngeal function objectively by measurement of the normalised glottal gap area (NGAA) or normalised rima glottides surface area (RGSA) via video laryngoscopy.…”
Section: Resultsmentioning
confidence: 99%
“…The agreement between assessors of laryngeal function was excellent in only one study [12]. Brown et al found disagreements in the assessment of laryngeal function, swallowing and the incidence of laryngospasm between direct and masked observers [10]. Also, disagreement between observers was reported by McKeirnan et al in 58% of the cases, with some dogs being classified by some observers as having laryngeal paralysis and healthy by others [16].…”
Section: Agreement Between Laryngeal Function Assessorsmentioning
confidence: 96%
See 3 more Smart Citations